Applying structural equation model to study the critical risks in ERP implementation in Indian retail. Issue 1 (6th February 2017) - Garg, Poonam; Khurana, Reema
Abstract : Purpose: In order to reduce the high failure rate of enterprise resource planning system (ERP) projects in Indian retail, project managers need to analyze and understand the impact of risk factor on ERP implementation. The purpose of this paper is to identify the key risk factors solely or primarily for the Indian retail sector. Furthermore, this study also analyzes the impact of risk factors in ERP implementation using the structural equation model (SEM) approach. "User risk, " "project management risk, " "technological risk, " "team risk, " "organizational risk, " and "project performance risk" are the examined factors. Design/methodology/approach: A theoretical model is created that explains the risk factors which may impact the success of ERP implementation. Hypotheses were also developed to evaluate the interrelationship between risk factors and success of ERP implementation. Empirical data are collected through survey questionnaire from practitioners such as project sponsors, project managers, implementation consultants, and team members who are involved in ERP implementation in the retail sector to test the theoretical model. Findings: Using the SEM, it is found that 40 percent of the variations in ERP implementation success can be explained with the help of the model suggested in the research study. The results of the study has empirically verified that "user risk, " "project management risk, " "technological risk, " "team risk, " "organizational risk, " and "project performance risk" factors are positively impacting ERP implementation success. All six hypotheses were supported by the results of the study. Research limitations/implications: The findings from this paper can provide greater understanding of ERP implementations. Researchers, practicing managers, and those seeking to implement ERP in retail organization can also use the findings of this study as a vehicle for improving ERP implementation success in the retail sector. Originality/value: The study integrates the impact of risk factor on ERP implementation. Very few studies have been performed to investigate and understand this issue. Therefore, the research can make a useful contribution.